2013
DOI: 10.1016/j.jastp.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Microtops II and satellite ozone measurements in the period 2001–2011

Abstract: a b s t r a c tDaily average total ozone Microtops measurements obtained during several campaigns conducted from 2001 to 2011 at latitudes from 31 to 681N and in different seasons are compared with satellite observations. The Microtops ozone is derived using different wavelength combinations (Channel I, 305.5/312.5 nm; Channel II, 312.5/320 nm; and Channel III, 305.5/312.5/320 nm). Satellite data from TOMS, OMI, GOME, and GOME-2 are used in the comparison. The three Microtops channels show a high correlation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Artuso et al, 2009;Becagli et al, 2012;Gómez-Amo et al, 2013). The results show that the PM 10 concentrations are influenced by marine and ship emissions to which Saharan dust events in spring are added (Becagli et al, 2012;Mallet et al, 2016).…”
Section: Sampling Of Insoluble Deposition and Total Mass Measurementsmentioning
confidence: 90%
“…Artuso et al, 2009;Becagli et al, 2012;Gómez-Amo et al, 2013). The results show that the PM 10 concentrations are influenced by marine and ship emissions to which Saharan dust events in spring are added (Becagli et al, 2012;Mallet et al, 2016).…”
Section: Sampling Of Insoluble Deposition and Total Mass Measurementsmentioning
confidence: 90%
“…Gómez‐Amo et al . () found good agreement and correlation between satellite observations and observations using three MICROTOPS. Srivastava et al .…”
Section: Resultsmentioning
confidence: 99%
“…Srivastava et al (2008) studied the daily variation in TCO, WV and AOT using MICROTOPS II observations and found a good agreement with the total ozone mapping spectrometer (TOMS) satellite data. Gómez-Amo et al (2013) found a good comparison and correlation between three MICROTOPS II and TOMS, the ozone monitoring instrument (OMI) and global ozone measurements experiment (GOME) satellites. Kalapureddy et al (2008) showed variations of TCO, WV and 34 S. Sharma et al…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Typical deviations of satellite measurements with respect to Brewer and Dobson instruments are around 2% (Gómez-Amo et al, 2013).…”
Section: Inputs For the Uver Rangementioning
confidence: 99%